Measurement of cross sections for production of a Z boson in association with a flavor-inclusive or doubly b-tagged large-radius jet in proton-proton collisions at √s=13 TeV with the ATLAS experiment - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Napolitano, Fabrizio; et al. (Physical review, 2023)
We present measurements of cross sections for production of a leptonically decaying Z boson in association with a large-radius jet in 13 TeV proton-proton collisions at the LHC, using 36 fb−1 of data from the ATLAS detector. Integrated and differential cross sections are measured at particle level in both a flavor inclusive and a doubly b-tagged fiducial phase space. The large-radius jet mass and transverse momentum, its kinematic relationship to the Z boson, and the angular separation of b-tagged small-radius track jets within the large-radius jet are measured. This measurement constitutes an important test of perturbative quantum chromodynamics in kinematic and flavor configurations relevant to several Higgs boson and beyond-Standard-Model physics analyses. The results highlight issues with modeling of additional hadronic activity in the flavor-inclusive selection, and a distinction between flavor-number schemes in the b-tagged phase space.